Dealing with Upper Secondary school students' anxiety in speaking lessons through a cooperative learning environment - Nguyễn, Thị Thanh Cảnh (ĐHNN, 2017)
Part one: Introduction. Part two: Development (Chapter 1: Literature review. Chapter 2: Research Methodology. Chapter 3: Results and discussions. Chapter 4: The course). Part three: Conclusion